Trotsky and his Position on the February Revolution and his Role in the Outbreak of the October Socialist Revolution in Russia (1917) - Al-Fartousi, Adel Hassan Dafar Saeed; Al-Salman, Inaam Mahdi Ali (Al-Adab Journal, 2023)
Leon Trotsky remains one of the distinguished revolutionary Marxist figures of the twentieth century. Together with Lenin, he led the October Socialist Revolution in Russia in 1917, the revolution that helped define the politics of the century as the first socialist revolution in the world. He was one of the most prominent Russian Marxist figures who witnessed the struggle for power in Russia since May-October 1917 The research deals with Trotsky's position on the February Revolution of 1917, which practically ended the Tsardom rule and the duality of power. The research shows Trotsky's political activity upon his return to Russia after ten years of absence. The research reviews his position on the Bolsheviks, Lenin, the Provisional Government and the Executive Committee of the Petrograd Soviet. The research focuses on the importance of the rhetorical agitation carried out by Trotsky, and his call for consensus between the various Russian socialist currents, and the research shows Trotsky's position on Kornilov 's coup. The research shows the central role that Trotsky played in building the premises of the October uprising of 1917, where he invested his election again as President of the Petrograd Soviet and from this position he incited and directly publicized the establishment of the Second All-Russian Congress of Soviets through the activities of the Soviets and others, and his leadership and direction of the Revolutionary Military Committee Which is one of the organs of the soviets, which succeeded in leading the uprising. The research clarifies Trotsky's role as an extremist defender of the Bolshevik uprising and the establishment of the Bolshevik Soviet rule in the face of the socialist opposition during the Second Congress of Soviets.